2007
DOI: 10.1088/0029-5515/47/9/028
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and modelling of external kink mode control using modular internal feedback coils

Abstract: We report on recent advances in modelling and experiments on resistive wall mode feedback control. The first experimental demonstration of feedback suppression of rotating external kink modes near the ideal wall limit in a tokamak is described [1]. This was achieved using an optimized control system employing a low latency digital controller and directly coupled modular feedback coils. The magnitude of plasma dissipation affecting kink mode behaviour has also been experimentally quantified for the first time u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Similarly, n ¼ 1 feedback experiments in HBT-EP have shown that when control coils at one out of the five toroidal positions are turned off, the reduction of RWM amplitude at that location is weaker than at the active locations. 178 This "non-rigid" behavior suggests coupling to other toroidal mode numbers. Coupling between toroidal modes can also be induced by non-axisymmetry of the resistive wall or other external conducting structures.…”
Section: E Feedback: Discussion and Challengesmentioning
confidence: 99%
“…Similarly, n ¼ 1 feedback experiments in HBT-EP have shown that when control coils at one out of the five toroidal positions are turned off, the reduction of RWM amplitude at that location is weaker than at the active locations. 178 This "non-rigid" behavior suggests coupling to other toroidal mode numbers. Coupling between toroidal modes can also be induced by non-axisymmetry of the resistive wall or other external conducting structures.…”
Section: E Feedback: Discussion and Challengesmentioning
confidence: 99%
“…Passive kink stability can be studied by moving the wall itself, instead of changing the location of the plasma with respect to a fixed wall. HBT-EP has also pioneered the use of active magnetic feedback to control the RWM [15][16][17][18][19]. RWMs have been suppressed or enhanced as a function of feedback parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The control of magnetohydrodyamic (MHD) instabilities with active feedback is a promising technique for maintaining the plasma confinement in nuclear fusion systems with improved economic viability [1][2][3]. Development of advanced feedback algorithms has been shown to reduce the number of necessary sensors and actuators, as well as the required control power, without compromising feedback performance [4][5][6][7][8][9], which translates directly to simpler engineering and increased economic efficiency of any fusion plant.…”
Section: Introductionmentioning
confidence: 99%